Recovery of Damages for Mental Anguish Relating to Death Grief: the Jurisprudence of Certain Common Law Jurisdictions - Lytvynenko, Anatoliy A. (Teisė, 2024)
Courts in Common Law jurisdictions usually did not grant the recovery of damages for mental suffering unaccompanied with a physical injury or other wrong until the late 19th century. However, the given maxim changed when American courts allowed recovering damages for mental suffering in cases of improper delivery (or non-delivery) of telegraph messages, which primordially related to the death or serious illness of close relatives. English courts also recognized nervous shock to be recoverable in a handful of cases of the late 19th – early 20th century. In the several subsequent decades, the world of Common Law witnessed a multitude of cases, where the plaintiffs managed to recover damages caused by disinterment of graves, maltreatment of cadavers, negligence in burials and similar causes, where injury to feelings was connected with the demise of a close relative, or, as proposed by the author of the article, for the matter of brevity, death grief. In England, the recovery of damages for mental suffering from death grief was recognized by the judiciary in the case of Owens v. Liverpool Corp. (1938), which became one of paramount cases on recovery of damages for mental suffering relating to death grief, whereas there is a multitude of legal precedents of such recognition in the United States, and the key precedent upon this subject in Canada is the case of Mason v. Westside Cemeteries, Ltd. (1996). The article discusses English, American and Canadian cases, where the given topic is invoked.
Keywords: recovery of damages; mental anguish; Common Law jurisdictions; Civil Law